The Effect of Trendiness and Entertainment in Social Media Marketing on Purchase Intention through Brand Awareness - Demas Muhammad Rijal; Muhammad Fachmi; Yusrab Ardianto Sabban (Journal of Digital Business and Innovation Management, 2026)
The rapid growth of TikTok in Indonesia has created intense competition among local fashion brands, yet high engagement does not always translate into sales. This study aims to analyze the influence of trendiness and entertainment in social media marketing on purchase intention, with brand awareness as a mediating variable. Adopting the Stimulus-Organism-Response (S-O-R) theory, this research employs a quantitative approach using Structural Equation Modeling (SEM) with Amos software and the Sobel test. Data were collected via online questionnaires from 200 Generation Z respondents who are active TikTok users, selected through a purposive sampling technique. The results indicate that trendiness and entertainment have a positive and significant effect on brand awareness. However, trendiness and entertainment have a positive but non-significant effect on purchase intention directly. Brand awareness is proven to have a positive and significant effect on purchase intention and plays a full role in mediating the influence of trendiness and entertainment on purchase intention. The study concludes that trendy and entertaining content on TikTok must build brand awareness first to trigger consumer purchase intention. These findings contribute to S-O-R theory by clarifying the essential role of the 'Organism' in converting social media stimuli into consumer responses in a fast-paced short-video environment.